Comparative Analysis of Players’ Perceptions on Good Governance in Athletics Federation and Badminton Association of India - Subedi, Madhu Sudhan; Kumar, S. Prem (HPE Forum, 2025)
This study compares the opinions of players within the Athletics Federation of India (AFI) and the Badminton Association of India (BAI) regarding governance dimensions to identify areas of strength and improvement. Utilizing a descriptive research design and statistical analyses, perceptions on various governance dimensions were collected from 350 respondents via standardized questionnaires. Significant differences were found in opinions across dimensions such as organization transparency, reporting transparency, democratic processes, control mechanisms, sports integrity, solidarity, and stakeholder representation. Stakeholder representation emerged as a critical dimension with notable disparities observed in both associations. The findings underscore the importance of tailored governance strategies to address specific concerns and enhance transparency, integrity, and stakeholder engagement within sporting organizations. The higher number of significant disparities observed in the BAI compared to the AFI suggests pronounced challenges in governance practices within the former, emphasizing the need for targeted interventions. Overall, the study provides valuable insights for guiding targeted governance reforms aimed at ensuring the sustainability and success of these sporting organizations.